2006
DOI: 10.1139/l06-038
|View full text |Cite
|
Sign up to set email alerts
|

Determination of transport parameters for heavy metal in residual compacted soil using two methodologies

Abstract: Values of the hydrodynamic dispersion coefficient and retardation factor obtained using the traditional and cumulative mass methods of column test analysis for zinc, manganese, and cadmium in a compacted soil are compared. The soil under study is from the B horizon of a residual gneissic tropical soil used for construction of the liner for the sanitary landfill in the District of Visconde do Rio Branco, Minas Gerais (MG), Brazil. To evaluate the behavior of landfill leachate heavy metals through the soil, soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…It is thus possible to conclude that Zn and Cd replaced the desorbed Mn on the soil adsorption sites. A Mn retardation factor of 18.8 was reported by Azevedo et al (2005), close to the average value presented in Table 6. Given the greater hydraulic conductivity values (10 -5 to 10 -6 cm s -1 ) in the work by Azevedo et al (2005) as compared to those in the present study (10 -6 to 10 -7 cm s -1 ), the mobility of Mn was found to be practically independent of soil hydraulic conductivity.…”
Section: Determination Of Transport Parameterssupporting
confidence: 79%
See 1 more Smart Citation
“…It is thus possible to conclude that Zn and Cd replaced the desorbed Mn on the soil adsorption sites. A Mn retardation factor of 18.8 was reported by Azevedo et al (2005), close to the average value presented in Table 6. Given the greater hydraulic conductivity values (10 -5 to 10 -6 cm s -1 ) in the work by Azevedo et al (2005) as compared to those in the present study (10 -6 to 10 -7 cm s -1 ), the mobility of Mn was found to be practically independent of soil hydraulic conductivity.…”
Section: Determination Of Transport Parameterssupporting
confidence: 79%
“…The fact that the leachate pH value remained above that of the influent solution may be due to the fact that ion exchange of metals by the bases adsorbed in the soil solid phase continued over the course of the test. It is believed that when sample saturation with all the metals is reached the leachate pH will tend to equal the influent pH, as was observed by Azevedo et al (2005). Cation leaching occurred due to substitution by heavy metals added to the soil.…”
Section: Percolation Of Contaminant Solutionmentioning
confidence: 83%
“…The column test aims to determine the transport parameters that interfere with the diffusion of contaminants by porous media in controlled laboratory conditions [6], [29] which reflect the real situation. This technique is extensively used to understand soil/contaminant interaction, but recently it has been applied in Portland cement matrices, such as soil-cement [13] and in mortars and concrete [12].…”
Section: Column Testmentioning
confidence: 99%
“…In Brazil, most of the laboratory tests for sanitary landfills are preventive, for bottom or cover liner design, using low permeability compacted tropical soils with or without flexible membrane liners (Ritter, 1998;Boscov et al, 2001;Leite & Paraguassú, 2002;Stuermer, 2005;Azevedo et al, 2006). This approach does not consider the older waste deposits, where the contaminants are in direct contact with the natural subsoil.…”
Section: Laboratory Tests For Geo-environmental Site Characterizationmentioning
confidence: 99%